Increasing Women's Digital Literacy to Prevent Cybercrime through Community Counseling - Dewi Primasari; Nurul Kamilah; Freza Riana; Erwin Hermawan; Jejen Jaenudin (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2026)
The development of information technology has driven increased social media use among various groups, including housewives. However, unwise use of social media can have various negative impacts, such as the spread of cybercrimes, hoaxes, privacy violations, and a decline in the quality of social interactions. This community service activity aims to improve digital literacy by educating women at the Majlis Ta'lim Al-Barokah Islamic study group on the wise use of social media. The method used is educational counseling with a lecture approach and interactive discussions. Evaluation done using pre-tests and post-tests on 30 participants. The results showed an increase in the average score from 2.7 to 4.13. Analysis using N-Gain yielded a score of 0.78, which is considered high. This indicates that the outreach activities were effective in increasing participants' understanding of the wise use of social media.